2020
DOI: 10.24191/ji.v15i1.266
|View full text |Cite
|
Sign up to set email alerts
|

Social-Media Addiction among Students at Public University

Abstract: Improvement in data-transfer speed and constant, continuous innovation in software and hardware, and humans’ communication and networking through social-media networking have become much easier and breezier. Complex and data heavy information, such as high-definition videos, can be shared with million other users all over the planet at the ease of fingertips in just 1/1000th second. For the above reasons, social media have become a handy, crucial, and effective tool for users to propagate and seek useful and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Rosario et al (2020) found that digital literacy is associated with respondents' online information seeking behaviour during the COVID-19 pandemic. Contrary to the common perception that users' interactivity heavily relies on social media for seeking information on a study conducted by Salleh (2020) found that respondents rarely use social media as their primary source of information. Most of the respondents did not depend on social media to find information.…”
Section: Introductioncontrasting
confidence: 58%
“…Rosario et al (2020) found that digital literacy is associated with respondents' online information seeking behaviour during the COVID-19 pandemic. Contrary to the common perception that users' interactivity heavily relies on social media for seeking information on a study conducted by Salleh (2020) found that respondents rarely use social media as their primary source of information. Most of the respondents did not depend on social media to find information.…”
Section: Introductioncontrasting
confidence: 58%
“…The theoretical review carried out questions the magnitude of the influence that new information and communication technologies may be having on young university students and how it affects their behavior, social habits, forms of relationship, daily tasks, and even in the psychological field, such as stress, anxiety, self-control, confidence, self-concept, etc. Numerous studies have warned of the consequences of Internet addiction in general and of social networks in particular on university students [79][80][81][82][83][84][85][86][87][88], affecting them on a personal and social level as well as on academic performance. It has even been determined that it is a determining factor that affects the quality of sleep [89][90][91][92][93], which is fundamental for health and especially for the adequate development of academic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Such as, for example, entertainment, including a wide range of web technologies as blogs, wikis, online social networks, and virtual networks [15]. In this idea, other recent studies have reported evidence of the level of SN addiction in university students [14], [18], [19], [20], [16]. These arguments give us support to think that the student populations are where this phenomenon occurs most frequently.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Currently, SN play an elementary role in the environment of young people, technological progress favors the use of this tool in the area of communication, contributing to the exploration of information, sharing and expressing opinions [13], [14], [15], [16]. Social networks are considered a "global consumption phenomenon" [14].…”
Section: Literature Reviewmentioning
confidence: 99%